Factors affecting the successful implementation and sustainability of the Liverpool Care Pathway for dying patients: a realist evaluation. Issue Volume 5: Issue (2015)Supplement 1 (7th November 2014) - McConnell, Tracey; O'Halloran, Peter; Donnelly, Michael; Porter, Sam
Abstract : Objectives: The Liverpool Care Pathway (LCP) for the dying patient was designed to improve end-of-life care in generalist healthcare settings. Controversy has led to its withdrawal in some jurisdictions. The main objective of this research was to identify the influences that facilitated or hindered successful LCP implementation. Method: An organisational case study using realist evaluation in one health and social care trust in Northern Ireland. Two rounds of semistructured interviews were conducted with two policymakers and 22 participants with experience and/or involvement in management of the LCP during 2011 and 2012. Results: Key resource inputs included facilitation with a view to maintaining LCP 'visibility', reducing anxiety among nurses and increasing their confidence regarding the delivery of end-of-life care; and nurse and medical education designed to increase professional self-efficacy, and reduce misuse and misunderstanding of the LCP. Key enabling contexts were consistent senior management support; ongoing education and training tailored to the needs of each professional group; and an organisational cultural change in the hospital setting that encompassed end-of-life care. Conclusions: There is a need to appreciate the organisationally complex nature of intervening to improve end-of-life care. Successful implementation of evidence-based interventions for end-of-life care requires commitment to planning, training and ongoing review that takes account of different perspectives, institutional hierarchies and relationships, and the educational needs of professional disciplines. There is a need also to recognise that medical consultants require particular support in their role as gatekeepers and as a lead communication channel with patients and their relatives.